Sweatshops, Opportunity Costs, and Non-Monetary Compensation: Evidence from El Salvador. - SKARBEK, DAVID; SKARBEK, EMILY; SKARBEK, BRIAN; SKARBEK, ERIN (American Journal of Economics & Sociology, 2012)
Using evidence from field interviews, this article examines the alternative employment opportunities of thirty-one sweatshop factory workers in El Salvador and their perceptions about what types of non-monetary benefits they receive in their current employment. Interview subjects provide insights into the benefits of their own and peers' employments, their next-best alternative employment, and other aspects of total compensation. We find that workers perceive factory employment to provide more desirable compensation along several margins.